Deteksi Financial Statement Fraud dengan Metode Beneish Ratio Index (Studi Kasus Perusahaan yang Melakukan Penawaran Saham Perdana (IPO) di Bursa Efek Indonesia Tahun 2018) - Nur Latifatussolikhah; Dwi Ari Pertiwi (JFAS : Journal of Finance and Accounting Studies, 2020)
This study aims to determine the detection financial statement fraud using beneish ratio index method on companies which do Initial Public Offering (IPO) listed on the Indonesian Stock Exchange in 2018. Type of this study was qualitative with descriptive approach. Sampling technique of this study was purposive sampling with the number of samples are 26 companies which do Initial Public Offering (IPO) listed on the Indonesian Stock Exchange in 2018. Data analysis technique used by calculated the ratio index, compared the ratio index with the parameter index, determined companies classified as manipulator, nonmanipulator, and grey company, calculated and percentage of companies classified. The results of this study that: (1) Companies classified as manipulator amounted to 9 companies or 34,6%. (2) Companies classified as nonmanipulator amounted to 16 companies or 61,5%. (3) Company classified as grey amounted to 1 company or 3,9%.